(untitled) (International Association of Biologicals and Computational Digest, 2023)
Lysimachia arvensis var. Caerulea L. is an annual, perennial herbaceous shrub, belonging to the family Primulaceae. It is commonly called a blue pimpernel. All parts of the plant have medicinal value; it is native to the Mediterranean region but dispersed worldwide as an introduced plant. The present study analyzed the presence of secondary metabolites and also their amount. The anti-oxidant assay such as DPPH and ABTS determine the reducing agent which is present in the plant. Anti-bacterial activity checked against the Pseudomonas bacteria is a 2 mm zone of inhibition at a concentration of 1mg/ml.